2010
DOI: 10.1111/j.1365-2249.2010.04290.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased numbers of immature plasma cells in peripheral blood specifically overexpress chemokine receptor CXCR3 and CXCR4 in patients with ulcerative colitis

Abstract: SummaryUlcerative colitis (UC) is a chronic inflammatory bowel disease featuring infiltration by plasma cells producing immunoglobulins. We have reported previously the specific and significant proliferation of immature plasma cells in the inflamed colonic and pouch mucosa of UC patients. The aim of this study was to characterize peripheral blood immature plasma cells and the migration mechanisms of such immature plasma cells to inflamed sites in UC. The characteristics of peripheral blood immature plasma cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
40
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 38 publications
(53 reference statements)
8
40
0
1
Order By: Relevance
“…32, 44 Yet it is not clear whether CXCR3 expressed by autoreactive B cells confers them with migratory properties that enable them to cause harm, either through antibody production or promoting inflammation through cytokine release. The existence of high frequencies of CXCR3 ϩ AFCs or memory B cells in the blood of patients with autoimmune disorders 16,17 supports the hypothesis that migration and survival of postmitotic self-reactive AFCs, or plasma cells, are favored at sites of chronic inflammation through a mechanism implicating CXCR3 ligands. 18,45 Thus, autoantibodies may be produced by fully differentiated long-lived CXCR3 ϩ plasma cells recruited and persisting in inflamed tissues.…”
Section: Ifn-␥/t-bet-dependent Cxcr3 Induction In B Cells 4557mentioning
confidence: 74%
See 1 more Smart Citation
“…32, 44 Yet it is not clear whether CXCR3 expressed by autoreactive B cells confers them with migratory properties that enable them to cause harm, either through antibody production or promoting inflammation through cytokine release. The existence of high frequencies of CXCR3 ϩ AFCs or memory B cells in the blood of patients with autoimmune disorders 16,17 supports the hypothesis that migration and survival of postmitotic self-reactive AFCs, or plasma cells, are favored at sites of chronic inflammation through a mechanism implicating CXCR3 ligands. 18,45 Thus, autoantibodies may be produced by fully differentiated long-lived CXCR3 ϩ plasma cells recruited and persisting in inflamed tissues.…”
Section: Ifn-␥/t-bet-dependent Cxcr3 Induction In B Cells 4557mentioning
confidence: 74%
“…14,15 CXCR3 ϩ AFCs and memory B cells were found at particularly high frequency in peripheral blood of patients with autoimmune diseases mediated by autoantibodies. 16,17 This suggests that selfreactive AFCs may be produced and/or attracted to and sustained in chronic inflammatory niches through a mechanism that involves CXCR3 and its ligands. 18 In mouse models for lupus erythematosus, AFCs are found in inflamed tissues.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that levels of CXCR4 and CXCL12 are up-regulated in patients with inflammatory bowel disease [92]. Lentiviral over-expression of CXCR4 in MSC resulted in enhanced homing to the inflamed colon and amelioration of disease severity in TNBS-treated rats [93].…”
Section: Msc Migration Towards the Intestinementioning
confidence: 98%
“…In one study, patients with SLE were found to have decreased non-switched memory B cells; however these cells had increased CXCR4 expression and elevated serum SLE auto-antibodies, suggesting that the B cells had a more plasma cell like phenotype [25]. In a study of patients with inflammatory bowel disease, patients with ulcerative colitis or Crohn's disease were more likely to have circulating peripheral blood immature plasma cells with higher CXCR4 expression [26].…”
Section: Emerging Markers-cues From Preclinical Modelsmentioning
confidence: 99%